Orality, literacy and performance in the ancient world : orality and literacy in the ancient world, volume 9 - Minchin, Elizabeth. (Mnemosyne, Supplements, 2012)
The ninth meeting in the international Orality and Literacy in the Ancient World series - in the fiftieth year since the publication in 1960 of Albert Lord's The Singer of Tales - took as its theme 'Composition and Performance'. This volume contains a selection of those papers, several of which illustrate methodologically innovative approaches to the act of composition, the nature of performance, and vocalization in text. Under consideration are Homer, Hesiod, Plato, Isocrates, the orators of the Second Sophistic, and Proclus. Cross-cultural studies include, amongst others, South Slavic epic and a text from the Sanskrit archive.